Answer:
The smaller number = -1
The larger number = 3
Explanation:
Let the smaller number = a
Let the larger number = b
The larger of two numbers is 6 more than 3 times the smaller.
b = 3a + 6........... Equation 1
If the twice the larger number is increased by 3 times the smaller, the result is 3.
2b + 3a = 3........ Equation 2
Hence:
We Substitute 3a + 6 for b in Equation 2
2b + 3a = 3
2(3a + 6) + 3a = 3
6a + 12 + 3a = 3
9a = 3 - 12
9a = -9
a = -9/9
a = -1
b = 3a + 6........... Equation 1
b = 3(-1) + 6
b = -3+ 6
b = 3
Therefore,
The smaller number = -1
The larger number = 3